Evaluation of Outcome Between Excisional Haemorrhoidectomy and Longo’s Technique (PPH) - Rahman, Md Atiar; lslam, Md Shahidul; Sheikh, Md Shahadot Hossain; Siddique, Md Ibrahim; Ullah, Md Ahsan; Murshed, Khandker Monzur (Journal of Surgical Sciences, 2019)
Objective: The introduction of a Longo’s technique for the treatment of haemorrhoids has the potential for less postoperative pain, a short operating time, rapid healing and an early return to full activity. The outcome of Longo’s technique was compared with that of current standard surgery in a randomized controlled study, and followed up two years. Methods: In a prospective randomized study, 140 patients requiring surgical treatment for haemorrhoids grade 2, 3 and 4 were assigned to either MMF (Milligan-Morgan, Park Ferguson) or PPH (Procedure for prolapse and haemorrhoids) 70 each. Operating time, frequency of postoperative analgesic intake, hospital stay, time to return to normal activity and postoperative complications were also recorded. Results: The Longo’s group had a shorter operating time, less frequent postoperative analgesia intake, and earlier return to normal activity. Postoperative pain at rest and during defecation was less important after PPH if no resection of external piles or skin tags was associated. After a mean follow-up of 24 months (12-46), recurrent haemorrhoidal symptoms, mostly mild and temporary, were reported after both MMF and PPH (Table-3). Four patients (5.71 %) complained of recurrent prolapse and/or external swelling after PPH, requiring re-do surgery in 3 of them between 18 to 32 months. Recurrent prolapse or external piles were also observed in 5 patients (7.14%) after MMF and re-do surgery was needed in 3 of them between 14 and 41 months. Long term patient's satisfaction after PPH was more or less same like after MMF. None of the patients had anal stenosis, incontinence, fecal urgency or sepsis. Conclusions: Postoperative pain is less after PPH. This advantage disappears if any resection is associated with the stapling. Use of a Longo's technique in the treatment of haemorrhoidal disease promotes rapid healing, shorter hospital stay and early return to normal activities. Journal of Surgical Sciences (2013) Vol. 17 (2) :66-72